Perbandingan Pakan Alami Berbeda terhadap Pertumbuhan dan Kelangsungan Hidup Benih Ikan Nila (Oreochromis Niloticus) - Mohammad Ilyas Yunus; Dewi Shinta Achmad; Indri Afriani Yasin; Tusaban Tusaban (Student Scientific Creativity Journal, 2026)
Nile tilapia (Oreochromis niloticus) culture requires an efficient and low-cost feeding strategy that can support fry growth and survival. This study aimed to analyze the effects of three types of natural feed, namely silk worms, earthworms, and snails, on absolute length growth, absolute weight growth, and survival of Nile tilapia fry. The study was conducted at the Aquaculture Laboratory, Faculty of Science and Computer Science, Universitas Muhammadiyah Gorontalo, from January 31 to March 2, 2026. An experimental method was applied using a Completely Randomized Design consisting of three treatments and three replications. A total of 45 Nile tilapia fry were reared in 9 plastic containers filled with 10 L of water, with 5 fish in each container. Growth and survival data were analyzed using ANOVA at the 5% significance level, while water quality was analyzed descriptively. The results showed that the type of natural feed had no significant effect on absolute length growth, absolute weight growth, and survival. Descriptively, silk worms produced the highest length and weight growth, with values of 2.99 cm and 6.37 g, respectively. Snails produced the highest survival rate of 86.66%. Water quality remained stable, with temperature ranging from 26.3 to 26.8°C, pH from 7.6 to 7.9, and dissolved oxygen from 5.2 to 5.6 mg/L. These findings indicate that silk worms are potential natural feed for improving growth, while snails support the survival of Nile tilapia fry.